Remodelações dialéticas em psicanálise: a nova origem imanente da diferença - Pozetti Filho, Fernando Alberto (2020)
This research goes through the dialectical universe and seeks, under such heuristic initiatives, to conjecture historical and current operators of human psychic functioning. Faced with the psychoanalytic field, throughout its first century of existence, we observed that it is inherent to its procedures of conceptual formalization and training of clinical praxis, a specific type of forging of concepts and technical rituals (settings) capable of precisely carrying out different guidelines of epistemologies, ontologies and languages. In this perspective, the association between dialectics and psychoanalysis will occur in the realization of new structures constituted by the principle of decentralization that emphatically pointed out the need to rethink theories of object relation, theories of memory, and modes of subjectivation and the very idiosyncrasy of its Ethics. Therefore, there was and will be successive modulations of metapsychologies since they operate as investments and divestments of systems capable of conceptualizing nuclear laws and transformation procedures, coupled with the direct designations of the psyche, the clinic, the culture, the language, the university. We trace an unusual historical path, in which the pre-Socratic and Aristotelian orientation starts to dialogue, to, dozens of centuries later, be revived by Hegel and, from there, by the irreparable transformations of thought and society in the 20th and 21st centuries. Finally, this text engages in discussions of the recent conquests of artificial neural networks, read, here, as heirs of this same dialectical logic. The general objective is to propose the genesis and to stimulate a new investigation path that, at the present moment of the discoveries of technoscience, allow to ratify assumptions of the history of the psychoanalytic movement and its metapsychologies, compacting them to the formal scope that gave life to artificial intelligence. It will be through operators such as tensors, topology and structural combinatory that this conjecture will be outlined in this research